ANALISIS YURIDIS TERHADAP PEMBAGIAN HARTA BERSAMA TANPA PERJANJIAN PRA-NIKAH PASCA PERCERAIAN BERDASARKAN PUTUSAN NO 108/PDT.G/2021/PN.SGR - Ni Komang Intan Kumala Sari; setianto, muhamad jodi; Adnyani, Ni Ketut Sari (Universitas Pendidikan Ganesha, 2025)
The phenomenon of patriarchal culture is still frequently encountered in the midst of community life. This is due to the societal belief that men are prioritized because they are the heirs of lineage. In this case, the author attempts to examine a legal case at the Singaraja District Court concerning alimony and undivided shared property. In the final decision, a larger proportion of the shared property is obtained by the male party due.to.the.absence of a prenuptial agreement that.regulates.the terms of marital property division. The purpose of this research is to analyze court decisions and understand how judges consider dividing shared property without a prenuptial agreement based on the Civil Code, Law Number 16 of 2019 regarding changes to Law Number 1 of 1974 concerning Marriage. Additionally, it aims to encourage society to be more mindful of creating prenuptial agreements before marriage to ensure the interests of both parties are accommodated. The research methodology employed in this study is a normative juridical approach, utilizing three types of approaches: case analysis, legal provisions, and conceptual analysis.